Mechanisms and Subseasonal Predictability of Unprecedented Multiple Tropical Cyclone Event in Autumn 2024 - Yitian Qian; Pang‐Chi Hsu; Yangyang Zhao; Hao Li (Geophysical Research Letters)
Abstract In autumn 2024 (late October to mid‐November), an unprecedented multiple tropical cyclone (MTC) event occurred over the western North Pacific (WNP). Six storms formed within a month, surpassing the climatological mean by 4 standard deviations. Four storms were simultaneously active—an event unmatched in 45 years. This anomaly was linked to exceptionally strong Madden–Julian Oscillation (MJO)‐related suppressed convection over the Indo‐Pacific warm pool, triggering a Kelvin wave response that enhanced cyclonic circulation and moisture convergence, and reduced vertical wind shear over the WNP. All subseasonal‐to‐seasonal models, including the ECMWF, deep learning FuXi‐S2S, and WNP TC hybrid models, predicted the active TC period beyond 4 weeks. Although ECMWF model struggled to predict the inactive‐to‐active transition, the other two models maintained predictive skill up to 4–5 weeks. A comparison of the ECMWF ensemble members that did and did not capture the MTC event showed that accurate MJO prediction is key to subseasonal MTC forecasting.